2008
DOI: 10.1088/0022-3727/41/22/225104
|View full text |Cite
|
Sign up to set email alerts
|

Optical polarization characteristics ofm-oriented InGaN/GaN light-emitting diodes with various indium compositions in single-quantum-well structure

Abstract: Spontaneously polarized light emission from m-plane InGaN/GaN light-emitting diodes was studied as a function of In composition in the InGaN single quantum-well layer. Emission wavelength was varied between 394 and 472 nm. A strong correlation was confirmed between optical polarization and In composition; the higher the In composition, the stronger the optical polarization. The photon-energy difference between the emission spectra associated with the two polarizations, ΔM, was evaluated as a function of curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 39 publications
4
42
0
Order By: Relevance
“…Third, the dependences of polarization ratio on current are different. The polarization ratio of PA is almost unity with current while that of m-plane spontaneous emission slight decreases as reported by Krame [30] and DenBaars [31]. Therefore, the PA is distinct from the spontaneous emission observed in m-plane in phenomenology.…”
Section: Resultssupporting
confidence: 68%
“…Third, the dependences of polarization ratio on current are different. The polarization ratio of PA is almost unity with current while that of m-plane spontaneous emission slight decreases as reported by Krame [30] and DenBaars [31]. Therefore, the PA is distinct from the spontaneous emission observed in m-plane in phenomenology.…”
Section: Resultssupporting
confidence: 68%
“…16 17 Evolution of stacking faults and dislocations in the sample was observed from the dark field TEM image of Figure 1(b). Using g · b extinction rules, when viewed along c-direction with g = −2110, partial dislocations (b = 1/5 20-23 ), threading dislocations (b a+c = 1/3 [11][12][13][14][15][16][17][18][19][20][21][22][23]), and prismatic stacking faults (R = 1/2 [10][11]) could be observed. It was clear that misfit dislocations and stacking faults are generated at the interface between InGaN and GaN layers.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Mutta et al [4] have reported the experimentally investigations using transmission electron microscopy and photoluminescence on WZ (In,Ga)N/GaN QW for various structure parameters. The effects Inconcentration on the optical properties of WZ (In,Ga)N/GaN QW [5] and on the optical polarization characteristics of m-oriented InGaN/ GaN QW LED [6,7] are investigated. On the other hand, some theoretical studies are reported.…”
Section: Introductionmentioning
confidence: 99%